Analytical framework and data for a municipal solid waste environmental performance assessment - Deus, Rafael M. [UNESP]; Mele, Fernando D.; Bezerra, Barbara S. [UNESP]; Battistelle, Rosane A.G. [UNESP] (Elsevier, 2020)
This article contains (i) a set of spreadsheets with data compiled from municipal sanitation or solid waste plans, and (ii) data of the individual and aggregate performance indicators. These indicators have been published in the Journal of Cleaner Production in the article entitled “A municipal solid waste indicator for environmental impact: assessment and identification of best management practices.” The data contained in the spreadsheets are divided as follows: worksheet 1 includes the municipal solid waste generation data from the Brazilian municipalities studied; worksheet 2 presents the individual indicators that form the aggregate indicator; worksheet 3 presents the aggregate indicator and the classification of the municipalities; worksheet 4 provides data correlation; worksheets 5 to 10 depict boxplot graphs of the data; and worksheets 11 to 14 present graphs of individual indicators on a per capita basis and the ranking of municipalities.
Keywords: Carbon dioxide equivalent; Environmental analysis; Indicators; Strategic waste management